Effects of supervisor's gender on American women's trust. - Jeanquart-Barone, Sandy; Sekaran, Uma (Journal of Social Psychology, 1994)
A study was conducted to examine the effects of supervisor's gender on American women's trust. Questionnaires were completed by 216 female civil service employees in a state university. Findings revealed that the women reporting to women trusted their supervisors significantly less than the women reporting to men did.